IMPLEMENTASI NILAI PEDULI SOSIAL MELALUI TRADISI TER-ATER MASYARAKAT SUKU MADURA PADA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI MTS AL IKLAS KUALA MANDOR B - Saiful Bahri; Emi Tipuk Lestari (Universitas Muria Kudus, 2020)
The purpose of this article is to analyze a) the tradition of the terrestrial Madurese community, b) the planning of the development of the value of social care through the terrestrial tradition in learning social studies. 3) Implementation of the development of the value of social care through the tradition of tererer in learning social science.This type of research is a Mixed Method with exploratory type (form) in the form of ethnographic research and classroom action research. Retrieval of data using observations, interviews, and documentation. The validity of the data is done by confirming the results of observations, interviews, documentation. Data credibility testing is done by extending observations, increasing persistence, triangulation of data, member checks, and references. Data analysis uses the interactive model of Miles and Huberman.The results showed that 1) Ter -ater means sharing fortune with relatives, neighbors, teachers and people who are considered worthy of delivery. 2) Planning the development of social care values through the Terterer tradition in social studies learning is carried out with the KD analysis in accordance with the tererier tradition is KD3.2. and KD.3.3. 3) The implementation of the development of the value of social care through this terrestrial tradition is carried out by using two-cycle class action research. Furthermore, the results of the study showed that the first cycle was held four times. In cycle 1 it was found that the teacher had not been able to reach the activities of all students in the class and the learning activities were still very much dominated by the teacher. In the implementation of cycle 2 using the value approach and the learning approach to do this can increase the value of student care through the tererated tradition. The enthusiasm of students can be seen well when assigned to be involved in the activities of tererer in their environment, and students can focus their attention on the material presented